2011
DOI: 10.1172/jci35721
|View full text |Cite|
|
Sign up to set email alerts
|

Human chronic myeloid leukemia stem cells are insensitive to imatinib despite inhibition of BCR-ABL activity

Abstract: Imatinib therapy, which targets the oncogene product BCR-ABL, has transformed chronic myeloid leukemia (CML) from a life-threatening disease into a chronic condition. Most patients, however, harbor residual leukemia cells, and disease recurrence usually occurs when imatinib is discontinued. Although various mechanisms to explain leukemia cell persistence have been proposed, the critical question from a therapeutic standpoint -whether disease persistence is BCR-ABL dependent or independent -has not been answere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
483
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(522 citation statements)
references
References 47 publications
24
483
0
5
Order By: Relevance
“…Here, we provided evidence that a subpopulation of cells, which exhibits the Docetaxel-resistance phenotype in cell lines and prostate cancer tissues, satisfied the T-IC criteria. These results corroborate a growing body of evidence (Corbin et al, 2011; Ishikawa et al, 2007; Lonardo et al, 2011; Todaro et al, 2007; Yu et al, 2007) that T-ICs may contribute to disease progression by participating in chemotherapy resistance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Here, we provided evidence that a subpopulation of cells, which exhibits the Docetaxel-resistance phenotype in cell lines and prostate cancer tissues, satisfied the T-IC criteria. These results corroborate a growing body of evidence (Corbin et al, 2011; Ishikawa et al, 2007; Lonardo et al, 2011; Todaro et al, 2007; Yu et al, 2007) that T-ICs may contribute to disease progression by participating in chemotherapy resistance.…”
Section: Discussionsupporting
confidence: 88%
“…A number of studies have shown that tumor-initiating cells (T-ICs) may preferentially survive exposure to chemotherapy, providing an attractive rationale for relapse following initial tumor shrinkage with standard therapy (Corbin et al, 2011; Ishikawa et al, 2007; Lonardo et al, 2011; Todaro et al, 2007; Yu et al, 2007). Having demonstrated that CK − cells survive Docetaxel exposure in vitro and in vivo, we investigated the tumor-initiating capacity of these cells.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis continues to be controversial. Moreover, there is a paucity of data suggesting that CSC are indeed resistant to targeted therapy 6 7…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study would also assess whether it is the leukemic stem cells, known to be resistant to TKI therapy, with increased levels of MSI2 that are responsible for the progression to BC [4]. Such cells are expected to be relatively scarce at diagnosis, but would be selected for and proliferate at the expense of others during the course of TKI therapy.…”
Section: Tablementioning
confidence: 99%